Patterns of Settlement of Cases of Domestic Violence Domestic Violence in Gayo Custom - Karmila; Taslim M. Yasin; Musdawati (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2020)
Domestic violence is any act against a person, especially women, that results in physical, sexual, psychological, and/or domestic neglect, including threats to commit acts, coercion, harassment, or unlawful deprivation of independence within the scope of the household. As stated in Article 1, Paragraph 1, of Law No. 23 of 2003 concerning the elimination of domestic violence, In the event of domestic violence, the settlement, although there is a law regulating domestic violence that requires the settlement process in court, still chooses customary law institutions to resolve domestic disputes. The people of Gayo Lues, in each gampong, have a customary institution that handles everything related to the interests of the community both internally and externally, namely the Geucik or penghulu. The community prefers to resolve cases of domestic violence through gampong customary institutions because the principles are in accordance with the values that have developed in the community. Customary law can resolve problems in a peaceful and easy way, and customary justice will realize the principles of kinship, peace, harmony, sincerity, and a strong sense of brotherhood. Settlement by customary law does not recognize defeat and victory and can even strengthen the bonds of brotherhood that were almost broken due to domestic violence. The pattern of resolving domestic violence cases resolved by Pak Geucik Gampong Penggalangan begins with a report from the victim or perpetrator, then, at a predetermined time, separate mediation is held by calling the victim or perpetrator in turn, after which mediation or deliberation is held simultaneously and a decision is made that has been agreed upon by both parties and outlined in an agreement letter.